Investigation of the Effect of Combined Drying for Rainbow Trout Fillets and Comparison with Hot-air Drying - Ismail, Osman; Kocabay, Ozlem Gokce (CENTRAL FISHERIES RESEARCH INST, 2020)
In this study, drying kinetics, chemical composition and surface color for fillets samples, namely Rainbow trout (Oncorhynchus mykiss) subjected to combined drying (ultrasonic assisted vacuum drying) and hot-air drying were compared at full length between 50-70 degrees C. Drying process carried out entirely in the falling rate period. The results suggested that the moisture content was influenced by the combined drying method and the drying temperature. The shortest drying time was obtained using combined drying method at 70 degrees C. The combined drying method made shorter the drying process and enhanced the effective moisture diffusivity by comparison with hot-air drying method. The activation energies were observed using a modified Arrhenius type equation as of 2.392 and 4.83 kW kg(-1) for combined and hot-air drying, respectively. Quality characteristics of fillets samples were specified as physical (moisture content, color values) and chemical (protein, fat and ash). Seven different drying models were considered for moisture ratios using nonlinear regression analysis. The consequences of regression analysis stated that the Midilli et al., model best fits data set. According to the results, the highest effective moisture diffusivity was determined in the fillets dried with the ultrasonic assisted vacuum drying method and they increased with increasing drying temperatures. Ultrasonic treatment accelerated the vacuum drying process for the fillets. Also, the ultrasonic assisted vacuum drying method is a better technology to preserve the original material and prevent thermal damage.
Keywords: Fish; Moisture content; Modelling; Color; COLOR CHARACTERISTICS; KINETICS; PRETREATMENT; ULTRASOUND; FOOD; Fisheries; Marine & Freshwater Biology